2014
DOI: 10.1002/jso.23639
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling in gastric cancer: Examining potential targets for chemotherapy

Abstract: MP of GC has the potential to define patients who would derive the greatest benefit from current therapies. Prospective controlled studies are required to validate the role of biomarkers in the management of GC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The implementation of the biomarker-driven therapy as reflected in our study is consistent with the increasing use of molecular analysis of tumors in oncology. The biomarker analysis results in the current cohort are overall consistent with those in a recent study involving 230 gastric cancer specimens, in which positive TOPO1 was reported for 68% of patients, negative TS for 63% of patients, high TOP2A for 60% of patients, and negative ERCC1 for 55% of patients [ 23 ]. Also, overall, our results are aligned with findings from recent studies describing the potential benefit of biomarker-driven therapy including studies in numerous tumor types such as pancreatic, breast, salivary gland, and others [ 7 – 12 ].…”
Section: Discussionsupporting
confidence: 89%
“…The implementation of the biomarker-driven therapy as reflected in our study is consistent with the increasing use of molecular analysis of tumors in oncology. The biomarker analysis results in the current cohort are overall consistent with those in a recent study involving 230 gastric cancer specimens, in which positive TOPO1 was reported for 68% of patients, negative TS for 63% of patients, high TOP2A for 60% of patients, and negative ERCC1 for 55% of patients [ 23 ]. Also, overall, our results are aligned with findings from recent studies describing the potential benefit of biomarker-driven therapy including studies in numerous tumor types such as pancreatic, breast, salivary gland, and others [ 7 – 12 ].…”
Section: Discussionsupporting
confidence: 89%
“…7,8 In the present study, a multiplatform approach was utilized that confirmed a high frequency of biomarker expression profiles that would suggest potential sensitivity to first line chemotherapeutic drugs. Interestingly, biomarkers such as RRM1, MGMT, PTEN, and SPARC were identified by IHC with increasing frequency, along with mutations including KRAS, PIK3CA, PTEN, ERBB2, BRAF, and EGFR, highlighting additional areas for targeted therapies.…”
Section: Discussionmentioning
confidence: 74%
“…Similar to genetic biomarkers, the analysis of common biomarkers of proteinaceous nature is highly informative in personalized cancer therapy. Examples of such biomarkers include the elevated expression of Topoisomerase I and 4E-Binding protein (p4E-BP1), which relate to a beneficial response to Topoisomerase 1 inhibitors and PI3K/mTOR inhibitors, respectively (14,15). On the contrary, multiple studies suggest that increased expression of the excision repair complementation group 1 (ERCC1) protein induces resistance to platinum-based chemotherapy (16)(17)(18).…”
Section: Molecular Analysis Of Protein Pharmacogenomic Biomarkersmentioning
confidence: 99%